On the behavior of solutions of operator-differential equations at infinity - Butyrin, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The existence of limits at the infinity, generalized in the Abel sense, is established for bounded solutions of the operator-differential equation y’(t) = Ay(t) in a reflexive Banach space.